PERANCANGAN BUKU CERITA BERGAMBAR “ THE ADVENTURE OF ARA “ - Ridha Utami; hendra afriwan (DEKAVE : Jurnal Desain Komunikasi Visual, 2020)
The role of parents is very important for children so they can be taught how to behave well and dare to be responsible. The purpose of designing the picture book "The Adventure of Ara" as an educational and communicative medium to instill children aged 5-7 years in the responsibility and not taking things that do not belong to them, due to the character development of children's responsibility that is not optimal, such as when children do not. return items that have been used or borrowed.The design method used in this picture storybook is the glassbox method, and for data collection, it uses interviews and questionnaires. Methods of data analysis using the 5W + 1H technique (when,why,who,what,where + how). To find a solution to the problem at hand. The design of the picture storybook “ The Adventure of Ara ” is also supported by other media such as posters, T-shirts, jigsaw puzzles, tumblers, coloring books, stickers, and also pins to support the main media.Keywords : Storybook, Responsible, Kids